Analisis Beban Pendinginan pada Gerbong Kereta Api Eksekutif (Studi Kasus KA. Argo Parahyangan) - Endang Permata Sari (Gorontalo Journal of Infrastructure and Science Engineering, 2021)
Train is a means of transportation with a large capacity and low transportation costs. The cooling system on trains has excess cooling load that passengers accept, causing discomfort for passengers. Analyzing and recommending a better cooling system according to existing standards is absolutely necessary by calculating the cooling load. The research objective was to determine the capacity of the air freshener machine in accordance with the needs of the train. The method used is the analytical method, where data collection is used as a research guide in solving problems. Collecting temperature data in an area to be calculated. The results obtained are the cooling load of executive passenger train carriages with a cooling load capacity design of 14899.86 Watt to 21.578.74 Watt and a cooling capacity of 34890 Watt. The cooling capacity when running the train is 8237.05 Watt and the actual total cooling load is 2445.8 Watt, so the total cooling capacity is relatively small. The actual conditions and design of the passenger space are within the comfort zone on the psychometric chart.